The Street Is My Pulpit : Hip Hop and Christianity in Kenya - Ntarangwi, Mwenda (Book collections on Project MUSE., 2016)
To some, Christianity and hip hop seem antithetical. Not so in Kenya. There, the music of Julius Owino, aka Juliani, blends faith and beats into a potent hip hop gospel aimed at a youth culture hungry for answers spiritual, material, and otherwise. Mwenda Ntarangwi explores the Kenyan hip hop scene through the lens of Juliani's life and career. A born-again Christian, Juliani produces work highlighting the tensions between hip hop's forceful self-expression and a pious approach to public life, even while contesting the basic presumptions of both. In The Street Is My Pulpit, Ntarangwi forges an uncommon collaboration with his subject that offers insights into Juliani's art and goals even as Ntarangwi explores his own religious experience and subjective identity as an ethnographer. What emerges is an original contribution to the scholarship on hip hop's global impact and a passionate study of the music's role in shaping new ways of being Christian in Africa [Publisher description].